2019
DOI: 10.1111/cpr.12584
|View full text |Cite
|
Sign up to set email alerts
|

C‐type lectin domain family 5, member A (CLEC5A, MDL‐1) promotes brain glioblastoma tumorigenesis by regulating PI3K/Akt signalling

Abstract: Objectives: Glioblastoma is the most common malignant glioma of all brain tumours.It is difficult to treat because of its poor response to chemotherapy and radiotherapy and high recurrence rate after treatment. The aetiology of glioblastoma is a result of disorders of multiple factors. Depending on cell signal transduction, these glioblastoma-associated factors lead to cell proliferation, differentiation and apoptosis.Therefore, investigation of the potential factors which involved in the development of gliobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…CLEC5A is a spleen tyrosine kinase-coupled receptor, which is abundantly expressed in monocytes, macrophages and neutrophils, and critical for inflammation response (31, 32). A recent study has shown that CLEC5A is upregulated in GBM significantly and is associated with poor prognosis (33). Furthermore, downregulation of CLEC5A can inhibit the capabilities of proliferation, migration, and invasion, and promotes apoptosis and G1 arrest in GBM cell lines (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CLEC5A is a spleen tyrosine kinase-coupled receptor, which is abundantly expressed in monocytes, macrophages and neutrophils, and critical for inflammation response (31, 32). A recent study has shown that CLEC5A is upregulated in GBM significantly and is associated with poor prognosis (33). Furthermore, downregulation of CLEC5A can inhibit the capabilities of proliferation, migration, and invasion, and promotes apoptosis and G1 arrest in GBM cell lines (33).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that CLEC5A is upregulated in GBM significantly and is associated with poor prognosis (33). Furthermore, downregulation of CLEC5A can inhibit the capabilities of proliferation, migration, and invasion, and promotes apoptosis and G1 arrest in GBM cell lines (33). These results are consistent with our findings that the expression level of CLEC5A increased with the ascent of risk scores and CLEC5A was a risk factor in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that the Akt/Bcl‐2 signaling pathway is related to apoptosis (Fan, Ni, & Fan, ). Thus, we evaluated the effect of engineered UC‐MSCs on p‐AKT and Bcl‐2 expression by IHC.…”
Section: Resultsmentioning
confidence: 99%
“…The genes in module 4 form a granular membrane and participate in neutrophil degradation, activation, and immune response. Among them, PLAU, CLEC5A, CD36 , and CD93 have been reported to affect the generation and development of gliomas [ 47 49 ]. VAMP8 is thought to promote the proliferation of glioma cells and lead to temozolomide resistance in human glioma cells [ 50 ].…”
Section: Discussionmentioning
confidence: 99%